The Effect of Financial Performance on Sustainability Report disclosure in companies listed on the LQ45 Index Of The Indonesian Stock Exchange (IDX) In 2018-2021 - Triharyati, Eri; Harokah, Mohammad Adha; Nurhayati, Yuli; Sari, Dian Wulan; Chandra, Revi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study aims to analyze the effect of financial performance by proxy ROA, ROE, NPM, PBV, and MarketCap on the disclosure of sustainability reports in companies listed on the LQ45 index of the Indonesia Stock Exchange (IDX). The data used is secondary data and the method used is panel data regression analysis with the help of the Eviews 12 program. The population in this study are companies listed on the LQ45 index on the Indonesian Stock Exchange, totaling 45 companies. The sample selection used a purposive sampling method. 15 companies meet the sampling criteria. The results of this study indicate that the ROA, ROE, NPM, PBV, and Market Capitalization have a significant effect on sustainability report disclosure and have samples from populations of the same variance. ROA and MarketCap variables have a negative and significant effect on sustainability report disclosure. The NPM variable has a positive and significant effect on the sustainability report disclosure. While the ROE and PBV variables do not affect the sustainability report disclosure. With an Adjusted R2 value of 39.16%.Penelitian ini bertujuan untuk menganalisis pengaruh kinerja keuangan dengan proksi ROA, ROE, NPM, PBV dan MarketCap terhadap sustainability report disclosure pada perusahaan yang terdaftar pada indeks LQ45 Bursa Efek Indonesia (BEI). Data yang digunakan merupakan data sekunder dan metode analisis yang digunakan yaitu analisis regresi data panel dengan bantuan program Eviews 12. Populasi dalam penelitian ini adalah perusahaan perusahaan yang terdaftar di indeks LQ45 Bursa Efek indonesia yang berjumlah 45 perusahaan. Pemilihan sampel menggunakan metode purposive sampling. Terdapat 15 perusahaan yang memenuhi kriteria sampling. Hasil penelitian ini menunjukan bahwa ROA, ROE, NPM, PBV dan Market Capitalization berpengaruh signifikan terhadap sustainability report disclosure dan memiliki sampel dari populasi dari varian yang sama. Variabel ROA dan MarketCap berpengaruh negatif dan signifikan terhadap sustainability report disclosure. Variabel NPM berpengaruh positif dan signifikan terhadap sustainability report disclosure. Sedangkan variabel ROE dan PBV tidak berpengaruh terhadap terhadap sustainability report disclosure. Dengan nilai Adjusted Â sebesar 39,16%.